Rhodobacterales and Rhizobiales Are Associated With Stony Coral Tissue Loss Disease and Its Suspected Sources of Transmission - Rosales, Stephanie M.; Clark, Abigail S.; Huebner, Lindsay K.; Ruzicka, Rob R.; Muller, Erinn M. (Frontiers in Microbiology, 2020)
In 2014, Stony Coral Tissue Loss Disease (SCTLD) was first detected off the coast of Miami, FL, United States, and continues to persist and spread along the Florida Reef Tractr (FRT) and into the Caribbean. SCTLD can have up to a 61% prevalence in reefs and has affected at least 23 species of scleractinian corals. This has contributed to the regional near-extinction of at least one coral species, Dendrogyra cylindrus. Initial studies of SCTLD indicate microbial community shifts and cessation of lesion progression in response to antibiotics on some colonies. However, the etiology and abiotic sources of SCTLD transmission are unknown. To characterize SCTLD microbial signatures, we collected tissue samples from four affected coral species: Stephanocoenia intersepta, Diploria labyrinthiformis, Dichocoenia stokesii, and Meandrina meandrites. Tissue samples were from apparently healthy (AH) corals, and unaffected tissue (DU) and lesion tissue (DL) on diseased corals. Samples were collected in June 2018 from three zones: (1) vulnerable (ahead of the SCTLD disease boundary in the Lower Florida Keys), (2) endemic (post-outbreak in the Upper Florida Keys), and (3) epidemic (SCTLD was active and prevalent in the Middle Florida Keys). From each zone, sediment and water samples were also collected to identify whether they may serve as potential sources of transmission for SCTLD-associated microbes. We used 16S rRNA gene amplicon high-throughput sequencing methods to characterize the microbiomes of the coral, water, and sediment samples. We identified a relatively higher abundance of the bacteria orders Rhodobacterales and Rhizobiales in DL tissue compared to AH and DU tissue. Also, our results showed relatively higher abundances of Rhodobacterales in water from the endemic and epidemic zones compared to the vulnerable zone. Rhodobacterales and Rhizobiales identified at higher relative abundances in DL samples were also detected in sediment samples, but not in water samples. Our data indicate that Rhodobacterales and Rhizobiales may play a role in SCTLD and that sediment may be a source of transmission for Rhodobacterales and Rhizobiales associated with SCTLD lesions.